Rivaroxaban versus warfarin in patients with atrial fibrillation enrolled in Latin America: insights from ROCKET AF - Blumer, Vanessa; Rivera, Manuel; Corbalán, Ramón; Becker, Richard C.; Berkowitz, Scott D.; Breithardt, Günter; Hacke, Werner; Halperin, Jonathan L.; Hankey, Graeme J.; Mahaffey, Kenneth W.; Nessel, Christopher C.; Piccini, Jonathan P.; et al. (American heart journal, 2021)
BACKGROUND: ROCKET AF demonstrated the efficacy and safety of rivaroxaban compared with warfarin for the prevention of stroke and systemic embolism (SE) in patients with atrial fibrillation (AF). We examined baseline characteristics and outcomes in patients enrolled in Latin America compared with the rest of the world (ROW). METHODS: ROCKET AF enrolled 14,264 patients from 45 countries. Of these, 1,878 (13.2%) were from 7 Latin American countries. The clinical characteristics and outcomes (adjusted by baseline characteristics) of these patients were compared with 12,293 patients from the ROW. Treatment outcomes of rivaroxaban compared with warfarin were also stratified by region. RESULTS: The annual rate of stroke/SE was similar in those from Latin American and ROW (P= .63), but all-cause and vascular death were significantly higher than in ROW (HR 1.40, 95% CI 1.20-1.64; HR 1.38, 95% CI 1.14-1.68; P< .001). Rates of major or nonmajor clinically relevant bleeding tended to be lower in Latin America (HR 0.89, 95% CI 0.80-1.0; P= .05). Rates of stroke and/or SE were similar with rivaroxaban and warfarin in patients from Latin America and ROW (HR 0.83, 95% CI 0.54-1.29 vs HR 0.89, 95% CI 0.75-1.07; interaction P= .77). CONCLUSIONS: Patients with AF in Latin America had similar rates of stroke and/or SE, higher rates of vascular death, and lower rates of bleeding compared with patients in the ROW. The effect of rivaroxaban compared with warfarin in Latin America was similar to the ROW. Further studies analyzing patient- and country-specific determinants of these regional differences in Latin America are warranted.